Effect of Educational Program on the "Quality of Life" of Family Caregivers of Patients Undergoing Hemodialysis - Golnar Ghane; Mansoureh Ashghali Farahani; Naima Seyed Fatemi; Hamid Haghani (Iran University of Medical Sciences, 2015)
Background: The family caregivers of patients undergoing hemodialysis have a major role in the care of patients at home. The study results indicate that these caregivers face with multiple problems regarding responsibilities and issues arising from the care and treatment of the patients.These issues decrease their quality of lives. However, these caregivers are mostly neglected andno studies are available on the effectiveness of educational program on their quality of lives. Therefore, this study aimed to examine the effects of educational program on the quality of life of family caregivers of patients undergoing hemodialysis. Methods: This research was a randomized controlled clinical trial, conducted on 76 family caregivers of patients undergoing hemodialysis referred to Shahid Hasheminejad, a medical and educational center in Tehran, Iran. The subjects were equally allocated into 2 groups of 38 patients.The caregivers of the patients who referred in even or odd days of the week were randomly assigned into the intervention and control groups, respectively. The intervention group received 4 training sessions on home care training program during 2 weeks, but the control group just received the routine training at the center. Both groups answered demographic information and "quality of life" (SF-36)questionnaires before and 6 weeks after the intervention. Then, the obtained data were analyzed in SPSS, 21. Descriptive statistics, the Chi-square and Fisher exact tests, as well as independent samples t-test, t-couple, and Mann-Whitney U test were used to analyze the data. Results: The majority of caregivers (54%) were in the age range of 35-55 years. About 68.4% were female and 70% were married. No significant difference was found between the baseline mean scores of "quality of life" of the intervention and the control groups (45.95±14.94 vs. 45.08±11.02, P=0.775). However, the mean scores of quality of life of the intervention group increased at the end of the study and the 2 groups were significantly different in this regard (63.51±11.55 vs. 41.74±10.51, P<0.001). Conclusion: The current study showed that home care training program can be effective in improving the quality of life and compatibility with the responsibilities of caregivers and change their lifestyle. Therefore, we suggest that managers of educational and medical center encourage their staffs to use such programs for improving the caregivers' health.